Perioperative Management in the Collegiate Athlete: An Integrated Approach - Rugg, Caitlin M.; Ginder, Jordan H.; Bharadwaj, Ananyaa; Vomer, Rock; Dale, Gregory A.; Ketterly, Jennifer; Zarzour, Hap; Amendola, Annunziato; Lau, Brian C. (Sports Medicine International Open, 2023)
Collegiate athletes face rigorous physical, academic, and emotional demands. While significant attention has been paid to injury prevention among young athletes in the past two decades, orthopedic injury rates remain high among collegiate athletes, and a significant number will undergo surgical management for injuries each year. In this narrative review, we describe techniques for perioperative management of pain and stress after surgery in collegiate athletes. In particular, we outline pharmacologic and non-pharmacologic management of surgical pain, with a goal of minimizing opiate consumption. We emphasize a multi-disciplinary approach to optimizing post-operative recovery in collegiate athletes help minimize reliance on opiate pain medication. Additionally, we recommend that institutional resources should be harnessed to support athletes in their well-being, from a nutritional, psychological and sleep standpoint. Critical to success in perioperative pain management is the communication among the athletic medicine team members and with the athlete and family to address pain and stress management and encourage timely, safe return to play.
Keywords: pain managment; collegiate athletes; multidisciplinary; team based care; opiate reduction